Validation of the British Thoracic Society Severity Criteria for Pediatric Community-acquired Pneumonia - Ambroggio, Lilliam (Pediatr Infect Dis J, 2019)
BACKGROUND: The British Thoracic Society (BTS) guideline for pediatric community-acquired pneumonia (CAP) outlines severity criteria to guide clinical decision-making. Our objective was to examine the predictive performance of the criteria on the need for hospitalization (NFH) and disposition. METHODS: This was a retrospective cohort study of children 3 months–18 years of age diagnosed with CAP in an urban, pediatric emergency department (ED) in the United States from September 2014 to August 2015. Children with chronic medical conditions, recent ED visits, and ED transfers were excluded. The main outcomes were interventions or diagnoses that necessitate hospitalization (ie, NFH) and disposition (eg, admit vs. discharge). Test characteristics, stratified by age, were calculated for each outcome. RESULTS: Of 518 eligible children, 56.6% (n = 293) were discharged from the ED with 372 children meeting at least 1 BTS criterion. Overall BTS criteria were specific but not sensitive for NFH nor for disposition. For children <1 year of age sensitive criteria included not feeding and temperature for NFH and tachycardia, cyanosis and not feeding for disposition. For children ≥1 year of age, tachycardia had a sensitivity of >0.60 for both outcomes. The areas under the receiver operator characteristic curves for predicting any BTS criteria was 0.57 for NFH and 0.84 for disposition. CONCLUSIONS: The BTS CAP severity criteria had fair to excellent ability to predict NFH and disposition, respectively. Although specific, the low sensitivity and poor discriminatory ability for NFH of these criteria suggest a need for improved prognostic tools for children with CAP.